The distribution of heterophilic antigens and their relationship with autoimmune diseases - Sun, Lijun; Wang, Nana; Feng, Yangmeng; Huo, Xueping; Feng, Qing; Zhao, Xiangrong; Li, Yan; Yan, Liting; Xie, Xin; Hu, Jun (Frontiers in Immunology, 2023)
Introduction Microbial infections are associated with the occurrence of autoimmune diseases, but the mechanisms of microbial infection inducing autoimmune diseases are not fully understood. The existence of heterophilic antigens between microorganisms and human tissues may explain part of the pathogenesis of autoimmune diseases. Here, we investigate the distribution of heterophilic antigens and its relationship with autoimmune diseases. Methods Monoclonal antibodies against a variety of microorganisms were prepared. The titer, subclass and reactivity of antibodies with microorganisms were identified, and heterophilic antibodies that cross-reacted with human tissues were screened by human tissue microarray. The reactivity of these heterophilic antibodies with different individuals and different species was further examined by immunohistochemistry. Results In this study, 21 strains of heterophilic antibodies were screened. The results showed that these heterophilic antibodies were produced due to the existence of heterophilic antigens between microorganism and human body and the distribution of heterophilic antigens had individual, tissue and species differences. Conclusion Our study showed that heterophilic antigens exist widely between microorganisms and human body, and the heterophilic antigens carried by microorganisms may break the immune tolerance of the body through carrier effect and initiate immune response, which may be one of the important mechanisms of infection inducing autoimmune diseases.